2004
DOI: 10.1080/00498250400000816
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and structural viability of precision-cut rat lung slices in culture

Abstract: 1. The principal objective was to evaluate the functional and structural integrity of precision-cut rat lung slices in culture over 72 h.2. Lung slices metabolized 7-ethoxycoumarin in a time-dependent fashion, the major metabolites being the sulphate and glucuronide of 7-hydroxycoumarin with very low levels of the free compound. Prior treatment of rats with b-naphthoflavone elevated markedly the rate of metabolism. The optimum slice thickness, as exemplified by the metabolism of 7-ethoxycoumarin, was about 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Precision-cut rat lung slices were prepared as previously described [15]. Briefly, lungs were perfused intratracheally with agarose (0.75% v/w) at 37 °C.…”
Section: Preparation and Incubation Of Slicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision-cut rat lung slices were prepared as previously described [15]. Briefly, lungs were perfused intratracheally with agarose (0.75% v/w) at 37 °C.…”
Section: Preparation and Incubation Of Slicesmentioning
confidence: 99%
“…The studies reported here were conducted in vitro utilising precisioncut lung slices [15] The principal advantages of this in vitro system are that it maintains tissue architecture and cell-cell communication, and allows the facile use of a wide range of concentrations of chemicals, that would otherwise necessitate large animal numbers for commensurate in vivo studies [16]. It is particularly suited to the lung, a heterogeneous tissue composed of many different cell types that differ markedly in their carcinogen-metabolising enzyme profile [17].…”
Section: Introductionmentioning
confidence: 99%
“…were prepared from cylindrical cores (8 mm) as described for the liver (Umachandran et al, 2004(Umachandran et al, , 2006. A pre-incubation of 60 minutes was carried out.…”
Section: Preparation and Incubation Of Precision-cut Tissue Slicesmentioning
confidence: 99%
“…The advantages of adopting this in vitro system, in comparison with other systems such as subcellular fractions and primary hepatocytes, have frequently been pointed out in reviews (de Kanter et al, 1999;Lerche-Langrand and Toutain, 2000). Slices have been prepared from a number of tissues including liver (Hashemi et al, 1999), lung (Umachandran et al, 2004), intestine and colon (van de Kerkhof et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For the production of lung slices, animals were killed by an overdose of sodium pentobarbital, and lungs were perfused intratracheally with agarose (0.75% v/w) at 37 °C. Agar was allowed to solidify, and lung slices (600 μm) were prepared from cylindrical cores (8 mm) as described for the liver [17]. For incubations exceeding 24 h, slices were placed in fresh medium every 24 h. Three different slice pools, comprising 4-10 slices, were used per time point.…”
Section: Dibenzomentioning
confidence: 99%